An eco-dialogical study of second language learners' World of Warcraft (WoW) gameplay. (March 2015) - Newgarden, Kristi; Zheng, Dongping; Liu, Min
Abstract: This exploratory research proceeds from the perspective that language is ecological and dialogical. We examined variables derived from eco-dialogical coding of an episode of World of Warcraft play involving three English learners. According to the Eco-dialogical model (Zheng, 2012 ), second language (L2) learners need to learn to take skilled linguistic action (Cowley, 2013 ), a process of realizing the values of physical, sociocultural and dialogical affordances in the environment. We employed Multinomial Logistic Regression to determine which of our variables were predictors for three types of values realizing; namely, wayfinding orienting to sociocultural norms and synergized values realizing of both wayfinding and orientation to sociocultural norms. The model we developed suggested that when communicative projects collectively entailed players' a) verbalizing with synchronized avatar action, b) attending to game rules and c) coordinating in anticipation of good future prospects, players were more likely to realize both values realizing types synergistically. In other words, players' skilled linguistic action of prospective coordination, combined with multimodal languaging and constrained by WoW game rules, together, were more likely to lead to dual values realizing. This finding suggests that dual values realizing evokes connections between real-time first-order physical movements and multimodal languaging with situation transcending practices (Linell, 2009) which are second-order rules, and other sociocultural and linguistic norms. Coupling this finding with our Eco-dialogical unit of analysis, communicative projects, we suggest that these language learners developed co-agency. We conclude that our model should be tested in future studies that seek to illuminate the contribution of a new Eco-dialogical understanding of L2 learning and the potential for learners to have high quality languaging experiences in multiplayer 3D game environments and other social semiotically rich contexts. Highlights: We examined English learners' languaging during play of World of Warcraft (WoW). Relationships between distributed, ecological and dialogical constructs were tested. Game rules, prospective coordination and languaging modality predicted values realizing. Multimodal languaging was a strong predictor of dual values realizing. Dual values realizing may lead to changes in the Eco-dialogical system, i.e., learning.